IMPROVING THE STUDENTS’ SPEAKING SKILL THROUGH REPORT ANIMAL TEXT BY ADOPTING NUMBERED HEAD TOGETHER STRATEGY AT THE ELEVENTH GRADE OF MAN 2 MODEL MEDAN - Achmad Ramadhan (JURNAL TARBIYAH, 2017)
This research was conducted by using Classroom Action Research (CAR). This research aimed to improve the students’ speaking skill through report animal text by adopting Numbered Head Together strategy. The subject of this research was the eleventh grade of IPS-2 (social class) MAN 2 Model Medan which consisted of 38 students. This research was conducted in two cycles which every cycle consisted of two meetings. Based on the speaking test, the students’ score kept improving in every cycle. In the pre-test, there were 10 students (26,32%) who has passed the test. In the post-test I, there were 27 students (71,05%) who has passed the test. In the post-test II, there were 31 students (81,57%) who has passed the test. From the students’ score in every cycle, it was could be concluded that students’ score keep improve in every cycle. Based on the data analyzed of observation sheet, interview report, and diary notes, it was could be concluded that the learning process run well and the students were active, enthusiastic and interested in learning speaking English. The result of the research showed that report animal text significantly could improve the students’ speaking skill at the eleventh grade of MAN 2 Model Medan.